Zapisz wyrażenia, nie używając nawiasów. Zredukuj wyrazy podobne.
a) 2a + (3a - 7) =
b) x - (2x - 3) =
c) 3x - (y - 2x) =
d) -(3a + 6) - 4 =
e) -(2x - 1) - (3x + 1) =
f) (4a - 7b) + (2a + 3b) =
g) (2p - r) + (2r - p) =
h) (x + y) + (x - z) + (z - y) =

2

Odpowiedzi

2010-02-07T09:25:35+01:00
A) 2a + (3a - 7) = 2a + 3a - 7
b) x - (2x - 3) = x - 2x + 3
c) 3x - (y - 2x) = 3x - y + 2x
d) -(3a + 6) - 4 = - 3a - 6 - 4
e) -(2x - 1) - (3x + 1) = - 2x + 1 - 3x - 1
f) (4a - 7b) + (2a + 3b) = 4a - 7b + 2a + 3b
g) (2p - r) + (2r - p) = 2p - r + 2r - p
h) (x + y) + (x - z) + (z - y) = x + y + x - z + Z - y
Najlepsza Odpowiedź!
2010-02-07T09:30:26+01:00
A . 2a+3a-7 = 5a -7
b. x - (2x - 3) = x-2x-3=-x-3
c) 3x - (y - 2x) =3x-y-2x=x-y

d) -(3a + 6) - 4 =-3a-6-4=-3a-10
e) -(2x - 1) - (3x + 1) = -2x+1-3x-1=-5x
f) (4a - 7b) + (2a + 3b) =4a-7b+2a+3b=6a-4
g) (2p - r) + (2r - p) =2p-r+2r-p=p+r
h) (x + y) + (x - z) + (z - y) =x+y+x-z+z-y=2x